My old Confederate home : a respectable place for Civil War veterans - Williams, Rusty, 1948- (University Press of Kentucky, 2010)
In the wake of America's Civil War, hundreds of thousands of men who fought for the Confederacy trudged back to their homes in the Southland. Some-due to lingering effects from war wounds, other disabilities, or the horrors of combat-were unable to care for themselves. Homeless, disabled, and destitute veterans began appearing on the sidewalks of southern cities and towns. In 1902 Kentucky's Confederate veterans organized and built the Kentucky Confederate Home, a luxurious refuge in Pewee Valley for their unfortunate comrades.